Left Ventricular Torsion Deformation in Atrial Septal Defect Patients Undergoing Transcatheter Device Closure - Abdul Razak; Maryam Said Mohd. Al Hajri; K Ranjan Shetty; Krishnananda Nayak (International Journal of Cardiovascular Practice, 2018)
Introduction: Atrial septal defects (ASD) considered being one of the known congenital heart diseases. ASD causes increased volume overload of the right heart. The purpose of this study was to evaluate left ventricular (LV) torsion deformation in ASD patients undergoing transcatheter device closure.Methods: All adult patients who underwent transcatheter device closure with ostium secundum ASD were included in the study. We assessed LV torsion in ostium secundum ASD patient’s pre and post device closure by using speckle tracking echocardiography.Results: A total of 37 patients (22 females and 15 males) were included in this study. The average age was 28 ± 19 years. LV peak basal rotation improved significantly (P = 0.028) in post transcatheter closure. LV torsion (2.88 ± 0.99˚/cm before vs. 3.40 ± 1.41˚/cm after closure, P = 0.009) and twisting (15.12 ± 4.69˚ before vs. 17.95 ± 6.21˚ after closure, P = 0.005) were statistically significant in post transcatheter closure. Volumetric assessment of LV including end-diastolic volume and systolic volume showed significant improvement (P = 0.02, P < 0.01) post device closure.Conclusions: The increased peak LV twisting and torsion was mainly attributed to the improved peak systolic clockwise rotation after ASD device closure. The LV twisting at a younger age was improved after the closure of ASD.